Vitamin D and dexamethasone inversely regulate parathyroid hormone-induced regulator of G protein signaling-2 expression in osteoblast-like cells - Hömme, Meike; Schmitt, Claus P.; Himmele, Rainer; Hoffmann, Georg F.; Mehls, Otto; Schaefer, Franz (Endocrinology, 2003)
The PTH/PTHrP receptor stimulates both adenylate cyclase- and phospholipase C-dependent signaling pathways via different G proteins. The biological actions of PTH on bone are modified by steroid hormones. PTH induces expression of regulator of G protein signaling (RGS)-2, a putative preferential inhibitor of Gq-mediated phospholipase C activation. We investigated whether steroid hormones interfere with PTH signaling by modulating PTH-induced RGS-2 expression in osteoblast-like UMR 106-01 cells.